Exercise-Induced Biological and Psychological Changes in Overweight and Obese Individuals: A Review of Recent Evidence. (6th February 2014) - Dinas, Petros C.; Markati, Aleksandra S.; Carrillo, Andres E.
Abstract : On a global scale, the most recent evidence indicates that over 400 million adults are obese while 20 million children and 1.6 billion adults are overweight. The World Health Organization reveals that, by the year 2015, 2.3 billion adults will be overweight and more than 700 million will be obese. In this review paper we summarized the current evidence to elucidate the impact of exercise training on biological and psychological health indices in overweight and obese individuals. Endocrine function indices that are discussed herein include leptin, adiponectin, growth hormone, and ghrelin levels. Psychological factors include anxiety and depression, body image, and motivation for exercise. Overall, exercise promotes physical and psychological health in overweight and obese individuals particularly because exercise-induced adaptations occur across a multitude of systems within the active human. The impact of exercise on specific biological and psychological health indices contributes to overall health in overweight and obese individuals.